High-order above-threshold photoemission from nanotips controlled with two-color laser fields - Seiffert, Lennart; Paschen, Timo; Hommelhoff, Peter; Fennel, Thomas (Journal of the Physics B: Atomic and Molecular Physics, 2018)
We investigate the process of phase-controlled high-order above-threshold photoemission from metallic nanotips under bichromatic laser fields. Experimental photoelectron spectra resulting from two-color excitation with a moderately intense near-infrared fundamental field (1560 nm) and its weak second harmonic show a strong sensitivity on the relative phase and clear indications for a plateau-like structure that is attributed to elastic backscattering. To explore the relevant control mechanisms, characteristic features, and particular signatures from the near-field inhomogeneity, we performed systematic quantum simulations employing a one-dimensional nanotip model. Besides rich phase-dependent structures in the simulated above-threshold ionization photoelectron spectra we find ponderomotive shifts as well as substantial modifications of the rescattering cutoff as function of the decay length of the near-field. To explore the quantum or classical nature of the observed features and to discriminate the two-color effects stemming from electron propagation and from the ionization rate we compare the quantum results to classical trajectory simulations. We show that signatures from direct electrons as well as the modulations in the plateau region mainly stem from control of the ionization probability, while the modulation in the cutoff region can only be explained by the impact of the two-color field on the electron trajectory. Despite the complexity of the phase-dependent features that render two-color strong-field photoemission from nanotips intriguing for sub-cycle strong-field control, our findings support that the recollision features in the cutoff region provide a robust and reliable method to calibrate the relative two-color phas
Keywords: nanotips; coherent control; two-color; photoemission